Construction and validation of an instrument to assess global reading comprehension in third graders - Gaytan-Lugo, Laura (2021)
According to national and international assessment results, there is a serious problem regarding global reading comprehension. However, there is disagreement over the instruments used to assess such skills. The goal of this study is to evaluate global reading comprehension in third graders. With the use of Confirmatory Factor Analysis (CFA), an instrument of 30 items and three factors was confirmed: main ideas, inferences, and contextualization of the concept; the instrument was applied to 803 students. We also found that the same construct is appropriate for different contextual variables (gender, shifts, and socioeconomic status). As result, CFA offers a satisfactory solution in both the factorial structure of the scales and the levels of internal consistency.